2012
DOI: 10.1097/qad.0b013e32834d697f
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 induces NALP3-inflammasome expression and interleukin-1β secretion in dendritic cells from healthy individuals but not from HIV-positive patients

Abstract: HIV-1 was able to induce a NALP3-inflammasome response in healthy individuals, indicating that this inflammasome could play a role in the first steps of HIV-1 infection; the consequent inflammatory process may be important for directing host immune response against the virus and/or disease progression. HIV-DC seemed to be chronically activated, but unresponsive against pathogens. Our findings could be of interest considering the ongoing research about dendritic cell manipulation and therapeutic strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 16 publications
11
55
0
Order By: Relevance
“…The secretion of the proinflammatory factor IL-1b requires instigation of the inflammasome by an activator. We found that F-HIV but not C-HIV induced the secretion of IL-1b in iDCs and PKR, recently identified as activator of the inflammasome, was upregulated by F-HIV, indicating that it could be the activator of the NALP3 inflammasome (45,46).…”
Section: Discussionmentioning
confidence: 88%
“…The secretion of the proinflammatory factor IL-1b requires instigation of the inflammasome by an activator. We found that F-HIV but not C-HIV induced the secretion of IL-1b in iDCs and PKR, recently identified as activator of the inflammasome, was upregulated by F-HIV, indicating that it could be the activator of the NALP3 inflammasome (45,46).…”
Section: Discussionmentioning
confidence: 88%
“…These findings suggest that NLRP3 can be activated by virus-encoded viroporins due to their ability to disrupt the cellular ion balance. In the context of human immunodeficiency virus (HIV) infection, NLRP3 inflammasome activation is observed during the early onset of the HIV disease and HIV infection has been shown to activate the NLRP3 inflammasome and IL-1b secretion in DCs from healthy individuals, but not in those from HIVpositive individuals [61]. In addition to the aforementioned viruses, several other RNA viruses have been reported to activate the NLRP3 inflammasome.…”
Section: Rna Virusesmentioning
confidence: 99%
“…It has bene reported that viral infection or viral RNA transfection can trigger NLRP3 inflammasome activation (15,17,60). However, none of the known components (NLRP3, ASC, and caspase-1) in the NLRP3 inflammasome has the ability to bind viral RNA.…”
Section: Ddx19a Is Identified As a Novel Component In Nlrp3 Inflammasomementioning
confidence: 99%
“…It has been demonstrated that viral infections can induce the NLRP3 inflammasome activation (10,17,(58)(59)(60). We then investigated whether the NLRP3-ASC-caspase-1 complex is formed in response to HP-PRRSV infection.…”
Section: Hp-prrsv Infection Induces Nlrp3-dependent Inflammasome Actimentioning
confidence: 99%